POTASSIUM AND MAGNESIUM DRUGS IN THE TREATMENT OF CARDIOVASCULAR DISEASES IN THE PRACTICE OF PRIMARY CARE PHYSICIAN - A. M. Shilov; M. V. Melnik; A. O. Osiya; A. S. Lishuta (Рациональная фармакотерапия в кардиологии, 2016)
Role of magnesium and potassium deficiency in the development of cardiovascular diseases and their complications is discussed. Results of studies on efficacy of magnesium and potassium drugs in cardiology practice are presented. Preventive role of potassium and magnesium in the progression of atherosclerosis, arterial hypertension, endothelial dysfunction and insulin resistance is shown. The advantages of combined magnesium and potassium drugs are shown.